Detecting fake news on Covid-19 using machine learning algorithms - Hossain, Farhan; Hasan, Md Zahid; Hasan, Sourov; Alam, Mobassherul; Shahana, Afrin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.